A review of the role of ethanol‐induced adipose tissue dysfunction in alcohol‐associated liver disease. (23rd September 2021) - Gopal, Thiyagarajan; Ai, Weilun; Casey, Carol A.; Donohue, Terrence M.; Saraswathi, Viswanathan
Abstract: Alcohol‐associated liver disease (AALD) encompasses a spectrum of liver diseases that includes simple steatosis, steatohepatitis, fibrosis, and cirrhosis. The adverse effects of alcohol in liver and the mechanisms by which ethanol (EtOH) promotes liver injury are well studied. Although liver is known to be the primary organ affected by EtOH exposure, alcohol's effects on other organs are also known to contribute significantly to the development of liver injury. It is becoming increasingly evident that adipose tissue (AT) is an important site of EtOH action. Both AT storage and secretory functions are altered by EtOH. For example, AT lipolysis, stimulated by EtOH, contributes to chronic alcohol‐induced hepatic steatosis. Adipocytes secrete a wide variety of biologically active molecules known as adipokines. EtOH alters the secretion of these adipokines from AT, which include cytokines and chemokines that exert paracrine effects in liver. In addition, the level of EtOH‐metabolizing enzymes, in particular, CYP2E1, rises in the AT of EtOH‐fed mice, which promotes oxidative stress and/or inflammation in AT. Thus, AT dysfunction characterized by increased AT lipolysis and free fatty acid mobilization and altered secretion of adipokines can contribute to the severity of AALD. Of note, moderate EtOH exposure results in AT browning and activation of brown adipose tissue which, in turn, can promote thermogenesis. In this review article, we discuss the direct effects of EtOH consumption in AT and the mechanisms by which EtOH impacts the functions of AT, which, in turn, increases the severity of AALD in animal models and humans. Abstract : Alcohol promotes adipose tissue (AT) dysfunction thereby contributing to alcohol‐associated liver disease (AALD). Ethanol induces oxidative stress and inflammation in AT. Ethanol increases lipolysis and inhibits lipogenesis in AT. Ethanol impairs the secretion of adipokines and, increases pro‐inflammatory cytokines in extracellular vesicles. Ethanol‐induced CYP2E1 plays a role, in part, in altering the storage/secretory functions of AT. Moderate alcohol promotes BAT activation and AT browning thereby upregulating thermogenesis. Understanding the crosstalk between AT and liver would be useful to identify novel therapeutics for AALD.